(untitled) (Environment & Health, 2020)
Objective: We substantiated the strategic directions of the development of public health care system of Ukraine on the basis of its main routine functions. Material and methods: We used the data of our previous studies and conducted a retrospective analysis of the scientific literature data on current issues of public health care. Results: A scheme of the comparative characteristic of the subsystems of the national health system: medical care and public health protection was developed on the basis of the analysis and generalization of the results of our own research, scientific literature data. The main functions of each subsystem were determined, that are of theoretical and practical importance for the further development of conception, strategy and program for them. The main directions of the Public Health Strategy of Ukraine have been prepared and the strategic directions for the development of the domestic public health system of Ukraine (PHS) based on its certain main functions have been developed. The national principle “Health Protection in all Policies of the State” was indicated to be the key step for the effective development of domestic PHS. This principle cannot be implemented without political commitment of senior government officials to the problems of care of public health. The own definition of “Public Health System” and “Health Protection in All State Policies” is presented.